1990
DOI: 10.1088/0029-5515/30/6/004
|View full text |Cite
|
Sign up to set email alerts
|

The fishbone instability in the DIII-D tokamak

Abstract: ABSTRACT. Although most DIII-D plasmas are stable to the fishbone instability, fishbones are sometimes observed when /3 p £ 1.5 and ^ 5 5 x 10 13 cm" 3 . These bursts are usually of minor significance operationally; however, under one condition, over 50% of the beam power was lost. The angle of beam injection has little effect on the virulence of the instability, suggesting that the fishbone instability in DIII-D is the ion diamagnetic branch of the internal kink.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…Sawtooth oscillations [26], fishbone instabilities [27][28][29], and magnetic ripple [30] cause perturbations of the magnetic field and distortions of the fast ions paths, which result in either rearrangement of fast ions within the plasma or ejection of the ions from the plasma region [30]. Magnetic ripple is the non-axisymmetric variation in the strength of magnetic field and the non-axisymmetric displacement of magnetic field lines around the toroidal circumference of tokamak as a result of the discrete toroidal field coils.…”
Section: Effects Of Sawtooth Oscillations Fishbone Instabilities Anmentioning
confidence: 99%
“…Sawtooth oscillations [26], fishbone instabilities [27][28][29], and magnetic ripple [30] cause perturbations of the magnetic field and distortions of the fast ions paths, which result in either rearrangement of fast ions within the plasma or ejection of the ions from the plasma region [30]. Magnetic ripple is the non-axisymmetric variation in the strength of magnetic field and the non-axisymmetric displacement of magnetic field lines around the toroidal circumference of tokamak as a result of the discrete toroidal field coils.…”
Section: Effects Of Sawtooth Oscillations Fishbone Instabilities Anmentioning
confidence: 99%
“…27 Ordinarily, the fishbone instability barely perturbs the D-D fusion reaction rate, indicating that the instability has little effect on beam-ion confinement. The observations 28 suggest that the DIII-D mode is a fluid instability 29 rather than an energetic particle mode. 30 In Ref.…”
Section: Iiib Effect Of Helical Fields and Low-frequency Mhdmentioning
confidence: 89%
“…30 In Ref. 28 it was erroneously reported that fishbones occasionally cause large beam-ion losses, but subsequent measurements 31 showed that TAE instabilities were primarily responsible.…”
Section: Iiib Effect Of Helical Fields and Low-frequency Mhdmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] It can be very dangerous, leading to expulsion of a considerable fraction (up to 50%) of energetic ions. 5 But, on the other hand, sometimes it is useful, being a trigger of formation of the internal transport barrier. 6 Typically, the fishbone instability is associated with an m = n = 1 perturbation (m and n are the poloidal and toroidal mode numbers, respectively) in the plasma core.…”
mentioning
confidence: 99%